Beam Shape Control System with Cylindrical Lens Optics for Optical Wireless Power Transmission - Kenta Moriyama; Kaoru Asaba; Tomoyuki Miyamoto (Energies)
Due to its narrow divergence, optical wireless power transmission (OWPT) is promising for long-distance transmission systems. In OWPT systems, matching the beam shape with the solar cell geometry is crucial for both efficiency and safety. When the light is incident at an oblique angle, the beam is distorted in an axial direction, which requires appropriate beam shape control. In this study, a cylindrical lens system was designed to ensure uniform and effective light beam irradiation, even under oblique incidence conditions. A numerical model of the optical system was constructed, and it was experimentally confirmed that the beam shape could be controlled within 5% error over a transmission range of 1 m. The optical system was integrated with solar cell detection for consistent target recognition and beam irradiation, and its functionality was experimentally validated. The results are useful for expanding the application and infrastructure design in OWPT.